PENGARUH BADAN USAHA MILIK DESA (BUMDes) MITRA JAYA MANDIRI TERHADAP PELAKU USAHA UMKM - Yahno Andika (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
Micro, small and medium enterprises (MSMEs) are one of the pillars of the economy in the country, especially for village level government. But it often exists did not get good support from the village government. Therefore, the government should involve the existence of Village-Owned Enterprises (BUMDes) to improve income of MSME actors so that they can contribute to the village economy. Body Village-Owned Enterprises have become a social economic and commercial pillar (commercial institution) for people who want to manage and develop potential and the need for villages to be used as business facilities to increase income village communities, as well as their contribution to providing and providing good social services. Meanwhile, as a commercial institution, the aim is to seek profits through offers local resources (goods and services) to the community. This research design uses Qualitative descriptive type and approach which emphasizes understanding approach to social phenomena from the perspective of the research subject. This research conducted in BUMDes Mitra Jaya Mandiri by involving BUMDes Management and MSME Actors as Data sources taken by means of interviews and questionnaires. The results of the research are that BUMDes BUMDes Mitra Jaya Mandiri supports the existence of MSMEs as one means to improve the community's economy.